Respostas da frequência cardíaca ao teste de 1RM e da modulação autonômica da frequência cardíaca no período de recuperação em indivíduos com fatores de risco para doenças cardiovasculares - Cazelato, Leonardo [UNESP] (2015)
Background: The Autonomic Nervous System (ANS) is responsible for cardiac rhythm modulation, since the action of the sympathetic and parasympathetic branches on the pacemaker cells of the sinus node causes increase and decrease, respectively, of heart rate (HR). A variation of HR in the rest to exercise transition may indicate how the parasympathetic nervous system behaves in the first seconds of muscle contraction, because an inhibition of vagal modulation on the sinus node occurs as an initial response of HR to exercise. A reduced heart rate variability (HRV) in rest condition may indicate abnormal adaptation of the ANS, which suggests poor physiological functioning. In individuals that have risk factors for cardiovascular disease, HR response during exercise and recovery take longer to reach ideal values, which may be attributed to inefficient parasympathetic modulation at the start of physical effort, greater sympathetic activity and after- exercise cardiac stress. Objective: To evaluate the magnitude of HR responses during effort using the one maximum repetition test (1RM), verify the relation between the magnitude of these responses and the behavior of HRV during rest condition, and investigate the behavior of HR and HRV during the recovery period of the test in individuals with risk factors for cardiovascular disease. Method: Our sample was made up of thirteen people, both men and women, aged 50-71, with risk factors for cardiovascular disease. Laboratory tests were made, we carried out anamneses, anthropometric evaluations, and recorded values of HR and RR intervals (iR-R) in rest condition and in moments prior to effort, during the effort, and in the 3-minute recovery after effort in the 1RM test protocol. Based on the HR and iR-R data we calculated the rest/exercise HR variation, the rest/recovery HR variation, the SD1 and RMSSD indexes of HRV in rest condition and during recovery. Results: We did not find significant differences...